Hypocholesterolemics Effects of Yam Tuber (Dioscorea hispida Dennst) flour on Male Wistar Rat with Hypercholesterol Diet - Maligan, Jaya Mahar; Estiasih, Teti; Sunarharum, Wenny Bekti; Rianto, Thomas (Jurnal Teknologi Pertanian, 2011)
Yam tuber (Dioscorea hispida Dennst) contains water soluble polysaccharides. Â Itis supposed that water soluble polysaccharides from yam functions as bioactivecompound to decrease blood cholesterol level. The hypocholesterolemic effect of watersoluble polysaccharides in yam tuber (Dioscorea hispida Dennst) flour on Wistar rats(Rattus norvegicus) lipid profile was investigated. Â  A two month old Wistar rats (Rattusnorvegicus) consisted of three groups (P0, P1 and P2) with five rats of each group wereadapted for one week by giving standard diet (AIN-93). P0 group was treated bystandard diet AIN-93M, P1 group was treated by standard diet and force feeding by eggyolk as cholesterol source, whereas P2 were given modified standard diet (AIN-93M withyam tuber flour). The weight and cholesterol level were measured in 4 weeks. Bloodwas drawn from eyes (retro orbital plexus) every week for analyzing cholesterol levels(total cholesterol, HDL, LDL cholesterol and triglycerides). Research showed thatstandard diet (AIN-93M) which is modified with yam tuber flour (P2) could decrease totalcholesterol as much as 15.37 mg/dL, 18.85 mg/dL of total triglycerides, and 14.24mg/dL of LDL-c level. Conversely this modified diet can increase the HDL-c level asmuch as 27.20 mg/dL.Keywords: hypocholesterolaemic, yam tuber flour, lipid profile, hypercholesterol diet,wistar rat